2021
DOI: 10.3390/ijerph18063007
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Two Types of Whole Body Vibration Platforms on Fibromyalgia. A Randomized Controlled Trial

Abstract: Whole body vibration has been proven to improve the health status of patients with fibromyalgia, providing an activation of the neuromuscular spindles, which are responsible for muscle contraction. The present study aimed to compare the effectiveness of two types of whole body vibrating platforms (vertical and rotational) during a 12-week training program. Sixty fibromyalgia patients (90% were women) were randomly assigned to one of the following groups: group A (n = 20), who performed the vibration training w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Twenty-nine articles were evaluated (figure 1). (12,13,14,15,16,17,18,19,20,24,30,31,32,34,36,37,39) In contrast, Sauch-Valmaña et al (21) , Merriwether et al (22) and Haugmark et al (23) found no significant differences in outcomes after physical activity programs and a multidisciplinary rehabilitation program. The Ernberg et al (25) study found no significant anti-inflammatory effects on fibromyalgia symptoms or clinical and functional variables after progressive resistance exercise or relaxation therapy.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Twenty-nine articles were evaluated (figure 1). (12,13,14,15,16,17,18,19,20,24,30,31,32,34,36,37,39) In contrast, Sauch-Valmaña et al (21) , Merriwether et al (22) and Haugmark et al (23) found no significant differences in outcomes after physical activity programs and a multidisciplinary rehabilitation program. The Ernberg et al (25) study found no significant anti-inflammatory effects on fibromyalgia symptoms or clinical and functional variables after progressive resistance exercise or relaxation therapy.…”
Section: Methodsmentioning
confidence: 96%
“…Flowchart for the review of the state of the art according to PRISMA methodology Several studies demonstrated significant improvements in the conditions of fibromyalgia patients through various physical treatment methods. These treatments included low-intensity exercise, stretching and resistance, core strengthening, Tai Chi, aquatic training, heavy weight exercise, Swiss ball exercise, telerehabilitation with aerobic exercise, physical activity programs, integrated physical training and cognitive-behavioral therapy, aquatic physical training, aerobic exercise, and vibration platform training (12,13,14,15,16,17,18,19,20,24,30,31,32,34,36,37,39). In contrast, Sauch-Valmaña et al(21) , Merriwether et al(22) and Haugmark et al(23) found no significant differences in outcomes after physical activity programs and a multidisciplinary rehabilitation program.…”
mentioning
confidence: 99%
“…Either a vibrating hand-grip device (Hand Arm Vibration) or a vibrating platform on which the subject is required to sit or stand (Whole-Body Vibration) can be used to undertake vibration training. The two prima-ry categories of vibrating platforms are platforms that vibrate in a vertical direction (vertical platform) and platforms that vibrate by rotating in a horizontal direction (oscillating platform) (20,21). There are primarily two ways to apply vibration to the targeted muscles: directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%